INFILTRATIVE ENDOMETRIOSIS WITH LESIONS OF THE RECTOSIGMOID ILEOCECAL COLON, RECTOVAGINAL SEPTUM. MULTIDISCIPLINARY APPROACH (CLINICAL CASE) - Ющенко, Марина Анатольевна; Ананьева, Татьяна Владимировна; Ооржак, Орлан Валерийович; Котова, Александра Алесандровна; Елгина, Светлана Ивановна; Мозес, Вадим Гельевич; Рудаева, Елена Владимировна; Железная, Анна Александровна (Medicine in Kuzbass, 2022)
Approximately 10 % of women worldwide suffer from endometriosis, mainly of reproductive age. Due to the fact that endometriosis can be asymptomatic, its true prevalence is difficult to assess. Taking into account the diversity of clinical symptoms: cyclic and chronic pain, infertility, abnormal uterine bleeding, dysfunction of neighboring organs and other complaints that reduce the quality of life, including the psycho-emotional status of women of predominantly reproductive age, endometriosis remains one of the most socially and demographically significant diseases requiring a multidisciplinary approach. This article describes a rare clinical case of infiltrative endometriosis with damage to the rectosigmoid, ileocecal colon, rectovaginal septum. Taking into account the multidisciplinary approach of obstetricians and gynecologists and surgeons, the optimal chosen management tactics of the patient was obtained a favorable outcome for the woman.